REACTION OF currn COMPLEX OF PHTHALIC HYDRAZIDE WITH OXYGEN AND NITROGEN DONOR LIGANDS (Biological Sciences - PJSIR, 1994)
The reaction ofCu(ll) complex of phthalic hydrazide of type [Cu(HPH)3 (HP)6lHP with acetyl acetone (acac),monoethanolamine (MEA) ethylenediamine (en) and bipyridine (bipy) gives mononuclear complexes of types[Cu(HPH)2(acac)2] HP(l), [Cu(HPH)2(MEA)2](II), [Cu(HPH2(en)J 2HP(III) and [Cu(HPH)(bipyMHP)]HP (VI)respectively and with aniline (An) and p.phenylenediamine (p.Phda) it gives binuclear complexes of types [Cu2(HPH)2(An)(H2 0) ]HP(lV) and [Cu2(HPH)2 (p .Phda) (HP)] (V) respectively. The complexes have been characterized on thebasis of IR and electronic spectral and magnetic properties.Ligand field parameters have been calculated. Analysis of electronic spectra, Dq Value and IR spectra stronglyindicate the presence of CuN204, CuN202 and CuN04, chromophores.